Quantum gravity - Kiefer, Claus, 1958- (Oxford : Oxford University Press, 2012)
The search for a quantum theory of the gravitational field is one of the great open problems in theoretical physics. This book presents a self-contained discussion of the concepts, methods and applications that can be expected in such a theory, unifying quantum theory with Einstein's theory of general relativity.
Previous ed.: 2007.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Quantum gravity